Towards an integrated systematic approach for ecological maintenance: Case studies from China and Russia. (July 2022) - Lai, Shuhui; Eladawy, Ahmed; Sha, Jinming; Li, Xiaomei; Wang, Jinliang; Kurbanov, Eldar; Lin, Qixin
Graphical abstract: Highlights: The ecological maintenance was studied based on ecological environment quality. The impacts of factors on RSEI were studied based on geographical detectors. We utilized the minimum cumulative resistance to construct ecological security. The study can contribute to global ecological security and sustainable development. Abstract: The world's ecological security has been significantly threatened because of the rapid growth of urbanization. Recently, the worldwide studies of ecological maintenance and ecological security have become of crucial scientific value as it ensures the balance between human needs and resources. In this paper, the ecological maintenance status of Pingtan Island, Songming County (China), and Yoshkar-Ola (Russia) was studied from the perspective of ecological environment quality and ecological security pattern. The remote sensing-based ecological index (RSEI) was used to study the ecological environment quality, and the geographic detector was used to analyze the impact of six factors on RSEI. The random forest algorithm was used to classify land use from remote sensing images, and an ecological security pattern was constructed based on the minimum cumulative resistance (MCR) model. The results show that the overall ecological maintenance of Pingtan Island is moderate, which accounts for 32.46% of the total area. The explanatory power of the dryness factor, which is the most influential factor on ecological environmental quality, increased by 3.90% during the five years, and the ecological corridor increased by 8.67 km. Songming County accounted for 33.66% of the area with moderate ecological maintenance. The dryness factor which affects the ecological environment quality is changed into the greenness factor, and its explanatory power has decreased by 3.59%, and the ecological corridor has increased by 57.95 km. Yoshkar-Ola accounted for 28.47% of the area with moderate ecological maintenance. The explanatory power of the dryness factor, which is the biggest factor affecting ecological environment quality, increased by 2.69% during the five-year period, and the length of the ecological corridor increased by 10.64 km. In this paper, remote sensing and GIS methods were used to integrate the ecological security status of inland and coastal areas and different natural zones and to conduct a comparative study on the ecological maintenance status of the three case studies, which can provide decision-making support for regional planning and contribute to global ecological security and sustainable development.